Lead (Pb2+) adsorption by monodispersed magnetite nanoparticles: Surface analysis and effects of solution chemistry. Issue 4 (December 2016) - Bagbi, Yana; Sarswat, Ankur; Mohan, Dinesh; Pandey, Arvind; Solanki, Pratima R.
Abstract: Monodispersed magnetite nanoparticles [Fe3 O4 -NPs] were synthesized by chemical co-precipitation using ferrous and ferric chloride as iron precursors. The composition, surface properties and morphology were investigated using X-ray powder diffraction, transmission electron microscopy, dynamic light scattering, scanning electron microscopy and Fourier transform infrared spectroscopy. Synthesized magnetite nanoparticles have zeta potential of +22.0 mV and an energy bandgap of 2.2 eV. These NPs were used for aqueous Pb 2+ removal at different initial pHs, equilibrium time, temperature and adsorbent/adsorbate concentrations. Pb 2+ adsorption was increased with rise in solution pH. Almost 100% Pb 2+ removal was achieved [at magnetite NPs dose: 0.2 g/L; Pb 2+ concentration: 50 mg/L; pH 5.0; shaking speed: 200 rpm; temperature: 25 °C and equilibrium time: 30 min]. Pseudo-first and pseudo-second order kinetic equations were applied to evaluate the kinetic data. Pseudo-second-order rate equation better fitted the data. Spent NPs were regenerated using 0.005 M HNO3 . Exhausted magnetite NPs were successfully recovered from aqueous system using a simple magnet. These magnetite NPs can also be used for Pb 2+ removal from waters having high concentration of suspended particles.